Knowledge, attitude and perception of Islamic religious leaders on maternal health issues in Zamfara state, Northwest, Nigeria: a qualitative study - Mohammed Mawaida, Abdullahi; Mamat, Nik Mazlan; Abdul Rahman, Suzanah; A. Rahman, Nor Azlina; Baba, Tukur (Partridge Publishing Singapore, 2017)
The objective of this study was to evaluate the knowledge, attitude and perception of the Islamic religious leaders (IRLs) on maternal health issues in Zamfara States, Nigeria, as well as the roles they can play in reducing maternal deaths in the state with a view to improve the maternal. A qualitative study, in the forms of in-depth interview and focus group discussion was conducted in eliciting information from the IRLs regarding their knowledge, attitude and perception on maternal health issues and maternal deaths among women of reproductive age in Zamfara State. A total of sixty four (64) IRLs were purposively sampled for this reason. The results show that all of the IRLs interviewed have a positive perception on maternal health issues and programs implemented by partners and donor agencies in maternal health services in the state, especially those with some knowledge about the activities of these implementing agencies. Their knowledge and understanding of the maternal health issues was high especially on maternal health issues from the Islamic perspectives and viewpoint. IRLs served as health educators on maternal health through delivering sermons at Friday congregational prayers (jummaat), Islamic gatherings and schools. In conclusion, the IRLs can become an important medium for information, education and communication in improving maternal health services uptake. Programmers, implementing agencies and donor partners in maternal health services need to collaborate and work with the IRLs in achieving the set targets of maternal mortality reduction and improving uptake of maternal health services in Zamfara.